2017
DOI: 10.1017/s1368980017000647
|View full text |Cite
|
Sign up to set email alerts
|

Low parental awareness about energy (calorie) recommendations for children’s restaurant meals: findings from a national survey in the USA

Abstract: Parent education about calorie recommendations for children could improve understanding and use of menu labelling information in restaurants. Targeted strategies are recommended to ensure that such efforts address, rather than exacerbate, health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This is similar to findings on fast food restaurants in previous studies. 22,47 Although fruit was an option in place of fries at 50% of the fast food restaurants in this study, which could reduce both the calorie and fat content of meals, previous research has found that these choices aren't popular. In 2011, McDonalds reported that although 80% of customers knew that they served apples slices instead of fries, only 11% of consumers in the U.S.A. made the apple choice.…”
Section: Discussionmentioning
confidence: 82%
“…This is similar to findings on fast food restaurants in previous studies. 22,47 Although fruit was an option in place of fries at 50% of the fast food restaurants in this study, which could reduce both the calorie and fat content of meals, previous research has found that these choices aren't popular. In 2011, McDonalds reported that although 80% of customers knew that they served apples slices instead of fries, only 11% of consumers in the U.S.A. made the apple choice.…”
Section: Discussionmentioning
confidence: 82%
“…However, the children’s meals still exceeded the recommended ≤600 calories/meal target and did not fully meet other nutrient targets [ 68 , 69 , 70 ]. Moreover, most parents are unaware of the energy recommendation of ≤600 calories/children’s meal [ 132 ], and many restaurant offerings exceed the recommended 700 calories/meal target for teens and adults.…”
Section: Discussionmentioning
confidence: 99%